Transnational migrations in the Asia-Pacific : transformative experiences in the age of digital media - Gomes, Catherine Jean; Yeoh, Brenda S. A. (Media, culture and communication in Asia-Pacific societies., 2018)
"This book uses digital ethnography to study critically the impact of digital media on transnational migrations, using case studies on diverse topics including transient migrants, gender and religion, ethnic migrants, refugees, intergenerational relationships, and transnational relationships across the borders of space and time"--